Study on the synergistic hydration mechanism of granulated blast furnace slag-carbide slag-based cementitious materials and the properties of full-solid waste backfill materials - Jianmin Li; Liwen Guo; Jiayong Zhang; Ye Li; Li Ma; Kai Wang (Scientific Reports)
Abstract The synergistic utilization of multiple solid waste is an effective means of achieving green filling and resource utilization of solid waste in mines. In this paper, the synergistic effects of solid waste granulated blast furnace slag (GS) and carbide slag (CS) as cementitious materials (GCCM) are investigated, along with their preliminary feasibility in combination with coal gangue (CG) and furnace bottom slag (FBS) for the preparation of backfill materials. The synergistic hydration mechanism, mechanical properties, working performance of GCCM and GBC were studied, and the environmental impact and cost-effectiveness of GBC were evaluated. The results indicate that when the molar ratio of n(CaO)/n(SiO2 + Al2O3) is 0.635 in GCCM, CS has a significant alkaline excitation effect on GS. In addition, the hydration products mainly composed of C-(A)-S-H gel, AFm and hydrotalcite. However, when the concentration of OH- is high in GCCM, Ca(OH)2 preferentially precipitates, leading to a reduction in the amount of main hydration product C-(A)-S-H gel. Moreover, GBC has better competitive strength performance than ordinary Portland cement (OPC). The optimal compressive strength of GBC at 28 days is 19.699 MPa, with a standard slump is 228 mm, fully meeting the strength and transportation requirements for mine filling. The heavy metal leaching rate at 28 days meets the requirements of GB 8978, demonstrating potential for carbon reduction and cost savings. The full-solid waste GBC developed in this study can replace cement as a backfill material, which is of significant importance for achieving green mining, the synergistic utilization of solid waste resources, reducing filling costs, and enhancing environmental benefits.